Building Dignified Worlds : Geographies of Collective Action - Roelvink, Gerda, 1978- (Book collections on Project MUSE., 2016)
Building Dignified Worlds examines how contemporary collectives are designing alternative economies. Contemporary collectives differ markedly from previous groups associated with revolutionary politics. Instead of assembling large groups of workers around labor issues, these new collectives creatively arrange diverse peoples, animals, natural environments, and technologies around economic concerns. Like older forms of leftist organizing, these collectives seek to bring about change. However, rather than working to overthrow and replace an underlying capitalist system with an equally totalizing alternative like socialism, they experiment with new forms of economic life. As Gerda Roelvink notes, current markets are better conceptualized as dynamic social networks open to intervention fey innovative social movements that do not simply protest but actively forge functional alternatives. Radical scholars have theorized social transformation as a performative act and have provided extensive analysis of how discourse shade the world through language and is materialized in bodies and practices. Until now through little has been written about the geographical nature of collective associations "performing" new worlds. Taking actor-network and performativity theories of action as starting points, Roelvink reveals how the relational and geographical nature of performative action is central to the ways in which hybrid collectives strive to create alternative economies.